Answer:
2(d-2)/(2d+1) or 1 - 5/(2d+1)
d can not be -½
Step-by-step explanation:
(d-3)/(2d+1) + (d-1)/(2d+1)
Lcm: 2d+1
(d-3+d-1)/(2d+1)
= (2d-4)/(2d+1)
= 2(d-2)/(2d+1)
If further simplification required:
= (2d-4)/(2d+1)
= (2d+1-5)/(2d+1)
= (2d+1)/(2d+1) - 5/(2d+1)
= 1 - 5/(2d+1)
2d+1 = 0
When d = -½
So d can not be -½ because when the denominator becomes 0, fraction becomes undefined
Hey there! :D
Substitute y for 5x-1.
3x+2y=11
y=5x-1
3x+2(5x-1)=11
3x+10x-2=11
13x-2=11
13x=13
x=1
Now, plug that in to find y.
y=5x-1
y=5(1)-1
y=5-1
y=4
(1,4) <== the solution
I hope this helps!
~kaikers
3500(1 + .03/12)^12(5)
3500(1.0025)^60
The answer is:
$4,065.66 or $4,066
Hope this helps :)
-4(9)(-5) = (-36)(-5) because -4(9) = -36. (-36)(-5) = 180